2022
DOI: 10.1111/hiv.13426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on HIV late diagnosis in a specialized German centre

Abstract: Background: The ongoing COVID-19 pandemic has been impeding HIV diagnosis and treatment worldwide. Data on the impact of COVID-19 on late diagnosis (LD) in Germany are lacking. Here we present novel data of a singlecentre German HIV cohort assessing LD during COVID-19. Methods: This is a non-interventional, single-centre retrospective cohort assessing the rate of LD comparing HIV diagnoses pre-COVID-19 with those during the COVID-19 pandemic. New diagnoses between 1 January 2019 and 1 February 2020 were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The increase in late-stage diagnoses 1 and 2 years after the pandemic supports this assertion. Van Bremen et al [7] found similar results, noting a higher likelihood of late diagnosis in Germany during the pandemic, an increased rate of HIV diagnoses during hospital admissions, and a reduction in diagnoses during routine check-ups.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The increase in late-stage diagnoses 1 and 2 years after the pandemic supports this assertion. Van Bremen et al [7] found similar results, noting a higher likelihood of late diagnosis in Germany during the pandemic, an increased rate of HIV diagnoses during hospital admissions, and a reduction in diagnoses during routine check-ups.…”
Section: Discussionmentioning
confidence: 67%
“…This disruption could potentially increase HIV transmission risks as fewer individuals were able to maintain undetectable viral loads [1]. By the end of 2021, reports of a rise in late HIV diagnoses from 2020 to the end of 2021 [7,8] illustrated the long-lasting effect of the pandemic on public health.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the experts suggested that only well-adjusted and engaged LPs should use the app. However, initial studies show that the number of LPs in Germany may have increased during the COVID pandemic [47,48]. Physicians should distinguish in each case whether an app can be useful or not.…”
Section: Organizational Conditionsmentioning
confidence: 99%
“…55 Various studies from other countries have also shown a delay in diagnosing HIV/AIDS during the COVID-19 pandemic. Reorganizing health services to focus on SARS-CoV-2 infection, reducing HIV screening tests, delaying or avoiding hospital or HIV testing center visits for fear of contracting SARS-CoV-2 infection, changing sexual behavior during the pandemic, misinterpretation of nonspecific HIV symptoms as SARS-CoV-2 infection findings or COVID vaccine side effects were the reasons attributed to reduced and delayed HIV diagnosis during the COVID-19 pandemic [55][56][57][58][59][60][61]. This study has several limitations.…”
mentioning
confidence: 99%